Rotational transitions in a C60 monolayer on the WO2/W(110) surface - SHVETS, IGOR; KRASNIKOV, SERGEY; LUBBEN, OLAF; MURPHY, BARRY; WU, HAN-CHUN; BULFIN, BRENDAN (My University, 2011)
Variable-temperature scanning tunneling microscopy (STM) is shown to be an effective technique to study two-dimensional phase transitions. Observations show that a monolayer of C60 deposited on an ultrathin WO2 layer grown on the W(110) surface undergoes a structural phase transition at 259 K, similar in temperature to that of bulk C60. In turn, a kinetic transition has been observed at 220 K, which is significantly higher than that of the bulk C60 crystal (90 K). This difference is attributed to interactions between the molecular overlayer and the substrate, as well as correlation effects within the C60 film. Different types of molecular nanomotion, such as rotation, spinning, and switching between different orientations, have been observed. STM measurements are supported by density functional theory calculations, which provide confirmation of different orientations of C60 on the WO2 thin film.
PUBLISHED
Keywords: Condensed matter physics; thin films; Nanoscience & Materials